The Development of a Virtual World Problem-Based Learning Tutorial and Comparison With Interactive Text-Based Tutorials - Jivram, Trupti; Kavia, Sheetal; Poulton, Ella; Hernandez, Aurora Sésé; Woodham, Luke A.; Poulton, Terry (Frontiers in Digital Health, 2021)
Collaborative learning through case-based or problem-based learning (PBL) scenarios is an excellent way to acquire and develop workplace knowledge associated with specific competencies. At St George's, University of London we developed an interactive online form of decision-based PBL (D-PBL) for our undergraduate medical course using web-based virtual patients (VPs). This method of delivery allowed students to consider options for clinical management, to take decisions and to explore the consequences of their chosen actions. Students had identified this as a more engaging type of learning activity compared to conventional paper-based/linear PBL and demonstrated improved exam performance in controlled trials. We explored the use of Second Life (SL), a virtual world and immersive 3D environment, as a tool to provide greater realism than our interactive image and text-based D-PBL patient cases. Eighteen separate tutorial groups were provided with their own experience of the same patient scenario in separate locations within the virtual world. The study found that whilst a minority of students reported that the Second Life experience felt more realistic, most did not. Students favored the simpler interaction of the web-based VPs, which already provided them with the essential learning needed for practice. This was in part due to the time proximity to exams and the extra effort required to learn the virtual world interface. Nevertheless, this study points the way towards a scalable process for running separate PBL sessions in 3D environments.